The employment effects of low-wage subsidies - Kristiina Huttunen; Jukka Pirttilä; Roope Uusitalo (Institute for the Study of Labor (IZA), 2010)
Low-wage subsidies are often proposed as a solution to the unemployment problem among the low skilled. Yet the empirical evidence on the effects of low-wage subsidies is surprisingly scarce. This paper examines the employment effects of a Finnish payroll tax subsidy scheme, which is targeted at the employers of older, full-time, low-wage workers. The system's clear eligibility criteria open up an opportunity for a reliable estimation of the causal impacts of the subsidy, using a difference-in-difference-in-differences approach. Our results indicate that the subsidy system had no effects on the employment rate. However, it appears to have increased the probability of part-time workers obtaining full-time employment.
Keywords: H24; J23; J68; 330; Low-wage subsidies; employment; social security contributions; Lohnsubvention; Niedriglohn; Wirkungsanalyse; Beschäftigungseffekt; Berufliche Integration; Finnland